SISTEM PREDIKSI RASA BUAH JERUK MENGGUNAKAN METODE k-NEAREST NEIGHBOR - Abdullah Abdullah; Kurnia Sandi (Universitas Methodist Indonesia, 2021)
Every buyer always wants to get a good product, including in terms of buyers of citrus fruits, but many buyers do not know how to choose sweet oranges if they have not been tasted first, so buyers usually experience disappointment when buying citrus fruits. The purpose of this study is to assist buyers in choosing citrus fruits, the k-NN method in identifying the taste of citrus fruits. The results of testing with the k-fold cross validation method obtained a value of 96.55%, while testing with the holdout method obtained a value of 91.67%. The benefit of this research is that by using the application that was built, buyers can predict the taste of citrus fruits without having to taste them first.